The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00795-016-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of IgA expression differentiates IgG4-related disease from plasma cell-type Castleman disease

Abstract: Plasma cell-type Castleman disease (PCD) is often encountered when differentiating IgG4-related disease (IgG4-RD). Given that serum IgA is often elevated in Castleman disease, we investigated whether IgA expression levels in histological specimens can be used to differentiate between the two diseases. Lymph node lesions obtained from 12 IgG4-RD and 11 PCD patients were analysed by immunohistochemistry with anti-IgG, -IgG4, and -IgA antibodies. In addition to all 12 cases of IgG4-RD, 8/11 cases (72.7 %) of PCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…11 A discussion about the overlap between IgG4-related disease (IgG4-RD) and iMCD led to consensus that iMCD should supersede a diagnosis of IgG4-RD, even with very high IgG4 levels, which is in agreement with recommendations from 2 IgG4-RD expert 43,44 Dense immunostaining of IgA in the lymph node and low serum IgG4/IgG also support a diagnosis of iMCD over IgG4-RD. 45 Hemophagocytic lymphohistiocytosis (HLH) shares significant overlap with iMCD, but our group decided that more data are needed to determine whether HLH should be excluded or considered an associated disease.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…11 A discussion about the overlap between IgG4-related disease (IgG4-RD) and iMCD led to consensus that iMCD should supersede a diagnosis of IgG4-RD, even with very high IgG4 levels, which is in agreement with recommendations from 2 IgG4-RD expert 43,44 Dense immunostaining of IgA in the lymph node and low serum IgG4/IgG also support a diagnosis of iMCD over IgG4-RD. 45 Hemophagocytic lymphohistiocytosis (HLH) shares significant overlap with iMCD, but our group decided that more data are needed to determine whether HLH should be excluded or considered an associated disease.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…We could not identify a case of TAFRO syndrome involving significantly elevated IgG4 levels (≥135 mg/dL), displaying an association with IgG4-related disease (IgG4-RD). Although IgG4-RD was denied according to the histopathological evaluation in the present case, differentiating IgG4-RD from CD is sometimes challenging [37]. Sato et al have analyzed six cases of MCD with abundant IgG4positive cells, meeting the criteria of IgG4-RD (IgG4/IgGpositive cell ratio, > 40%), and they have concluded that serum IL-6 and CRP elevation was more frequent in patients with MCD than in those with IgG4-RD [38].…”
Section: Discussionmentioning
confidence: 72%
“…It is sometimes difficult to distinguish PCD from IgG4-RD, as they have similar histological features including plasma cell infiltration in the interfollicular areas; additionally, PCD patient lymph nodes can also exhibit abundant infiltration of IgG4-positive cells. 11,12 Specific characteristics have been reported as useful in differentiating PCD from IgG4-RD, including the presence of IgA-positive cells in PCD, and eosinophilic infiltration observed in IgG4-RD. 11,13 Furthermore, hemosiderin deposition appears to be useful in differentiating between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: hemosiderin deposition; plasma cell-type Castleman disease; IgG4-related disease; serum IL-6; serum C-reactive protein differentiate PCD from IgG4-RD. 11 Furthermore, PCD frequently presents with variable lesions infiltrated by large numbers of IgG4-positive plasma cells, accompanied by high serum IgG4 levels. 11,12 Moreover, hemosiderin deposition has regularly been observed in lymph node lesions of PCD patients.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation